Functional Outcome in C2/C3 Fracture Dislocation Managed with Combined Surgical Decompression and Posterior Stabilization - Teuku Nanta Aulia; Muhammad Iqbal; M irfan Guranda (Jurnal Health Sains, 2023)
Spinal cord injury is one of the main reasons for permanent paralysis and immobility till now. Spine injury is usually fatal because it involves more than one component, such as discoligamentous misconfiguration, vascular and spinal cord damage. Spine dislocation fracture at the level of C2-3 is rare and usually affects one or two vertebras. Good functional outcome in spine injury is uncommon in which death almost always happens suddenly or is caused by secondary trauma. Emergency room with a cervical spine injury. The patient was pushed by his friends from the side during playtime, causing the neck to hit the corner of a table. The dislocation fracture at the level of C2-3 and spinal cord compression directly caused tetraplegia. The condition was handled with a decompression procedure, spine fusion at the level of C1-4, and posterior stabilization with pedicle screws. A day after the operation, minimal movements were seen in both arms and legs, with motoric strength of 2/2/2/2. The score improved to 4/4/4/4 after two weeks of meds and physiotherapy. The patient started to write again in week 3. The dislocation fracture in this patient caused spinal cord compression. A retropulsion fracture fragment can be displaced to the spinal canal and potentially cause further spinal cord damage. Displacement towards the anterior horn leads to motoric dysfunction. Dislocation fracture at the level of C2-3 hinders neurotransmitter impulse, causing total paralysis on all extremities with intact sensory function. The patient had temporary external stabilization around the neck area while waiting for the procedure. The management concept in cases like this includes affected spinal cord decompression and internal fixation using pedicle screws to ensure fracture stabilization.